Radial Interplanetary Magnetic Field‐Induced North‐South Asymmetry in the Solar Wind‐Magnetosphere‐Ionosphere Coupling: A Case Study. Issue 2 (14th February 2022) - Park, Jong‐Sun; Shi, Quan Qi; Shi, Xueling; Shue, Jih‐Hong; Degeling, Alexander W.; Nowada, Motoharu; Tian, An Min; Kim, Khan‐Hyuk; Pitkänen, Timo; Zhang, Yongliang
Abstract: In this paper, we present a case study of the radial interplanetary magnetic field (IMF B x )‐induced asymmetric solar wind‐magnetosphere‐ionosphere (SW‐M‐I) coupling between the northern and southern polar caps using ground‐based and satellite‐based data. Under prolonged conditions of strong earthward IMF on 5 March 2015, we find significant discrepancies between polar cap north (PCN) and polar cap south (PCS) magnetic indices with a negative bay‐like change in the PCN and a positive bay‐like change in the PCS. The difference between these indices (PCN‐PCS) reaches a minimum of −1.63 mV/m, which is approximately three times higher in absolute value than the values for most of the time on this day (within ±0.5 mV/m). The high‐latitude plasma convection also shows an asymmetric feature such that there exists an additional convection cell near the noon sector in the northern polar cap, but not in the southern polar cap. Meanwhile, negative bays in the north‐south component of ground magnetic field perturbations (less than 50 nT) observed in the nightside auroral region of the Northern Hemisphere are accompanied with the brightening and widening of the nightside auroral oval in the Southern Hemisphere, implying a weak, but clear energy transfer to the nightside ionosphere of both hemispheres. After the hemispheric asymmetries in the polar caps disappear, a substorm onset takes place. All these observations indicate that IMF B x ‐induced single lobe reconnection that occurred in the Northern Hemisphere plays an important role in hemispheric asymmetry in the energy transfer from the solar wind to the polar cap through the magnetosphere. Key Points: Hemispheric asymmetries in magnetic activity and ionospheric convection in the polar cap are observed under strong interplanetary magnetic field (IMF) B x conditions Weak, but clear energy transfer to the nightside auroral region is observed in both hemispheres during the same period IMF B x ‐induced single lobe reconnection may give rise to hemispheric asymmetry in SW‐M‐I coupling in the polar cap